Daya Gabung Inbred Jagung Pulut untuk Pembentukan Varietas Hibrida - Santoso, Sigit Budi; H.G, M. Yasin; Faesal, Faesal (Jurnal Penelitian Pertanian Tanaman Pangan, 2014)
Plant breeder utilizes performance of the experimental hybrid to study the effect of inbred parents on the hybrid development. Combining ability analyses using diallel mating indicates the potential heterosis effect on their hybrid combinations, which could be used in the breeding programs. Griffing’s model II was used to measure the responses of F1 hybrids relative to the parents and the overall F1 performances. The experiment consisted of 8 waxy corn inbred parents each was crossed in half-diallel combinations, resulting of 36 entries, including the inbred parents. The entries were set in a randomized complete block design with two replications, 2 rows (5 m) for each plot. Research was conducted in Gowa District of South Sulawesi from April to July 2012. The objectives of the research were to obtain the phenotypic correlation, General Combining Ability (GCA), Spesific Combining ability (SCA) and the heterosis effect of the parents. Results showed there were significant effects of genotypes on all traits, except for the number of kernels per ear row. The highest phenotypic correlation for grain yield was with the ear diameter (r = 0.86). The GCA effect among genotypes for grain yield was not significant, but for the 1,000 seed weight, ear length, and ear diameter, each was significant. The highest GCA was obtained by P8, of 38,375 for 1,000 seed weight. The SCA was significant for yield and yield components, except for the row number per ear and kernel per ear row. The highest SCA was indicated by P1xP5, and the hybrid yielded 2.29 t/ha, with the mid parents heterosis of 71%. But, the highest grain yield of the hybrid was obtained by P4 x P8 of 2.32 t/ha with 51% heterosis. Based on the yield and SCA value, two spesifik hybrid combinations (P1 x P5; P4 x P8) were considered a good potential for waxy corn hybrid development